Slippage reconfiguration of trinucleotide repeat hairpins impedes resolution by human replication protein A - Yu-Chi Kuang; Szu-Yu Chen; Hao-Yen Chang; Cheng-Wei Ni; Peter Chi; I-Ren Lee (Proceedings of the National Academy of Sciences, 2026)
Abnormal expansions of trinucleotide repeats (TNRs) are a major cause of neurodegenerative diseases, often driven by the formation of stable hairpin structures that interfere with protein machineries in DNA cellular processes. On the other hand, human replication protein A (hRPA) plays a central role in stabilizing single-stranded DNA and resolution of secondary structures. Understanding how hRPA interacts with TNR hairpins has become crucial to uncovering the mechanisms that regulate TNR stability. Here, we employed single-molecule fluorescence resonance energy transfer to investigate the interaction between hRPA and CTG repeat hairpins of varying lengths. We found that blunt-end hairpins impede hRPA resolution, while the presence of a short overhang facilitates initial binding followed by invasion. At higher repeat lengths, hRPA binding induces partial hairpin resolution, followed by conformational slippage that restores blunt-end hairpin structures and hinders further progression. Hairpin resolution is coordinated by the interplay of the multiple dynamic binding modes of hRPA and the slippage reconfiguration of the TNR hairpins. Moreover, our results reveal a concentration- and stoichiometry-dependent resolution process, herein full resolution of TNR hairpins with pathologically relevant repeat lengths requires protein concentrations exceeding physiological levels, potentially contributing to disease pathogenesis.